A Feasibility study on Quikstor a "virtual" quick response code-enabled supermarket with delivery and pick-up service - Dela Cruz, Leo Karlo C.; Losanes, Jeffrey C.; Magsombol, Joshua Jeremy S.; Nagrampa, Michelle C. (College of Engineering, 2013)
Virtual shoping is becoming a trend for the Filipinos nowadays based from a technology from Tesco Home Plus in South Korea. QR-code enabled virtual supermarket was born. By partnering with medium to large supermarkets to create virtual stores, setting up these stores to places with high human traffic (such as terminals, train stations, etcetera), end-users buying supermarket items using their smartphones (via a smartphone app), and delivering these purchases right to their homes, Quikstor was born. This study aims to see if it is feasible for the Filipino market. The marketing study shows that since almost no one has tried this venture yet, there is a big gap Quikstor can enter into. Filipinos are engaging more to virtual shopping so setting up a new virtual shopping experience would get a positive response. By engaging medium to large scale supermarkets and online advertising, Quikstor will be able to reach the market. Details of the venture were further discussed in the technical study. Different aspects of Quikstor, as well as how each stakeholder relate to all of the business process were elaborated. Costs of running Quikstor were determined and together with the projected sales of Quikstor, it was concluded that Quikstor is a sustainable venture. Roles and responsibilities of each Quikstor employee were elaborated in the organizational study. For the first five years of the company, Quikstor has three departments-marketing and sales, operations and IT department. Funding and cash flows were analysed in the financial study to see how much Quikstor needs in order for it to be started. It was determined that Quikstor will loan for the first three years of its operation, with each amount getting smaller every year, to lessen big amount of needed money from its investors. Lastly, the social profitability analysis proved that in order to give grocery shopping experience both to the mass market and as an alternative business set-up to supermarket companies proved that it has a high positive impact on the community.